2010
DOI: 10.1128/jb.01277-09
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Silver(I) on the Metabolism of Shewanella oneidensis

Abstract: Anaerobic cultures of Shewanella oneidensis MR-1 reduced toxic Ag(I), forming nanoparticles of elemental Ag(0), as confirmed by X-ray diffraction analyses. The addition of 1 to 50 M Ag(I) had a limited impact on growth, while 100 M Ag(I) reduced both the doubling time and cell yields. At this higher Ag(I) concentration transmission electron microscopy showed the accumulation of elemental silver particles within the cell, while at lower concentrations the metal was exclusively reduced and precipitated outside t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 44 publications
5
24
0
2
Order By: Relevance
“…3) could be due to the capping by proteins. This is in agreement with previous results [31] which reported that Ag + is reduced during the metabolism of anaerobic cultures of Shewanella oneidensis in presence of high Ag + concentrations (100 μM) and the NSAg forms in aggregates. The crystalline nature of the Ag nano-particles was also confirmed by the powder XRD pattern (Fig.…”
Section: Characterization Of Nsagsupporting
confidence: 94%
“…3) could be due to the capping by proteins. This is in agreement with previous results [31] which reported that Ag + is reduced during the metabolism of anaerobic cultures of Shewanella oneidensis in presence of high Ag + concentrations (100 μM) and the NSAg forms in aggregates. The crystalline nature of the Ag nano-particles was also confirmed by the powder XRD pattern (Fig.…”
Section: Characterization Of Nsagsupporting
confidence: 94%
“…Due to its versatile nature, it has been used for the bioreduction of various metals -uranium, chromium, iodate, technetium, neptunium, plutonium, palladium, selenite, tellurite, vanadate [31], silver [32,33] -and the oxides of manganese and iron [34]. Here we report on the reduction of aurate (III), using S. oneidensis seeded with aqueous Au 3+ ions at ambient temperature and pressure to produce stable Au 0 .…”
Section: Introductionmentioning
confidence: 95%
“…When this concentration was lowered to 10 µmol L −1 , bacteria survived and were able to keep the Ag(0) out of the cell, and precipitated it on the cell wall. 31 So in the case of Ag, intracellular precipitation was seen at higher concentrations and extracellular precipitation at lower concentrations.…”
mentioning
confidence: 96%